Analisis Buku Ajar Bahasa Arab Modern Dalam Perspektif Kurikulum Merdeka: Studi Kualitatif Pada Mahasiswa Pendidikan Bahasa Arab - Ijtihada Zahrani; Wafirotul Qudsiyyah; Ahmad Nur Mizan (Advances In Education Journal, 2026)
This study analyzes modern Arabic textbooks from the perspective of the Merdeka Curriculum. The problem addressed is the inconsistency between textbook content and the curriculum principles of flexibility, student-centered learning, contextual relevance, and differentiated instruction. This research aims to examine the suitability of textbook content, teaching approaches, assessment, and language-skill integration with the Merdeka Curriculum framework. A qualitative descriptive method with a library research and content analysis approach was employed. Data were collected through documentation and literature review of Arabic language textbooks and supporting academic references. The findings reveal that modern Arabic textbooks generally align with communicative approaches, language-skill integration, and curriculum flexibility; however, aspects of differentiated learning, HOTS-based assessment, and digital media integration remain insufficient. The study implies the need for developing more adaptive, contextual, and technology-supported teaching materials. In conclusion, continuous textbook innovation is essential to optimize Arabic language learning implementation within the Merdeka Curriculum.